Effect of adding methods of potassium sulfate fertilizer to two cultivars of Zea mays on PH and some chemical elements in soil and plants - Kahraman H. Habeeb (Zien Journals, 2023)
A field experiment was applied in the fall season in Wasit province/ Qalaat al-Suwaira District). The great soil aggregates (Typictorrifurert) according to the American classification (Soil Taxonomy) (1975). In order to improve the performance of growth and yield of Zea mays by the effect of fertilization with potassium sulfate on the availability of nutrients in the soil. The experiment was applied according to a randomized complete block design (RCBD) with a factorial experiment and with three replications. Ground fertilization, foliar fertilization, ground fertilization+ foliar fertilization, and control have been studied. The results have been showed that the fertilization treatment (ground + foliar fertilization treatment) was significantly superior in each of the pH in the period of 100 days, the available potassium concentration in the soil, the available sulfur concentration in the soil at 100 and 80 periods. The highest available nitrogen concentration in the soil in the 100 and 80 period, in fertilization Foliar, while the treatment (foliar fertilization) was significantly superior in the concentration of nitrogen in the plant, while the concentration of potassium in the plant, sulfur in the plant, was significantly superior in the period 100 in the fertilization of ground and foliar. For the nitrogen in the plant and the potassium in the plant, it has been recorded the highest averages in the ground fertilization, as well as the superiority of both sulfur in the soil and sulfur in the plant. The American Gentex variety was significantly superior and gave the highest averages in the pH. Sulfur in the soil, nitrogen in the soil, potassium in the soil, nitrogen in the plant, sulfur in the plant, potassium in the plant were significantly superior to the interaction treatment (ground + foliar fertilization of American Gentex variety). It has been found the highest averages in each of potassium in the soil, nitrogen in the soil, phosphorus in the soil, potassium in the soil, while the combined treatment (ground fertilization + foliar and American Gentex) achieved the highest averages in each degree of soil interaction, magnesium in the soil, Magnesium in the plant, sulfur in the plant, nitrogen in the plant.
Keywords: potassium sulfate; fertilizer; Zea mays; PH; magnesium